Kelimpahan Populasi Lalat Buah (Bactrocera spp.) dan Persentase Serangannya pada Buah Labu (Cucurbita maxima Duch) di Rovinsi Bali - DHEAR ANANDA SEMBIRING MAHA; DWI WIDANINGSIH; NI NENGAH DARMIATI (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
The Abundance of Fruit Flies (Bactrocera spp.) and the Percentages of Damage on Pumpkins (cucurbita maxima duch) in Bali Province The research of population a bundance and percentase of damage of bactrocera spp on pumpkin plants in Bali Province was carried out in ordel to determine the abundance of adults insect population and percentase of damage of this insect. The field regencies was connected in Bangli, Gianyar and Badung regencies and was crutimued in the Integrated Laboratory of Pest and disersaes Faculty of Agriculture, Udayana University, from February until April 2019. This research showed that the species was found to attack pumkins in the field were Bactrocera cucurbitae. The abundance of adult insect was calculated based on each fruit grades. The abundance on grade 5-10, 11-15, 16-20 >20 cm were 529, 239, 140, and 90, respectively. The of percentage of damage was calculated in lack vergency, where the sampling take place. The percentage of damage in Gianyar, Badung, and Bangli were 34%, 28%, and 30%, respectively.